Associations between parental well-being and early learning at home before and during the COVID-19 pandemic: observations from the China Family Panel Studies - Dong, Shuyang; Rao, Nirmala (Frontiers in Psychology, 2023)
Background: COVID-19-related lockdowns and preschool closures resulted in many young children spending all their time at home. Some parents had to manage child care while working from home, and increased demands may have led them to experience considerable stress. Evidence indicates that among parents with young children, those who had pre-existing mental and physical conditions adapted less well than other parents. We considered associations between parental well-being and the home learning environment for young children. Method: We leveraged data from the nationally representative China Family Panel Studies. We analyzed longitudinal data collected before (2018) and during (2020) the pandemic. Participants were parents of 1,155 preschoolers (aged 3~5 years in 2020). Moderated mediation models were conducted. Maternal and paternal psychological well-being, depression, physical health, and physical illness in 2018 and 2020 were predictors. The frequency of marital and intergenerational conflicts in 2020 was mediators. Primary caregiver-reported engagement in home learning activities and family educational expenditure and parent-reported time spent on child care in 2020, were outcome variables. The number of COVID-19 cases in each province three months before the 2020 assessment was the moderator. Child, parental and household characteristics and urbanicity were covariates. Results: Controlling for covariates, improvements in parental psychological well-being predicted more home learning activities and increases in paternal depression predicted less time spent by fathers on child care. Negative changes in maternal physical health predicted less family educational expenditure and longer time mothers spent on child care. Family conflicts mediated the association between maternal physical illness in 2018 and family educational expenditure. The number of COVID-19 cases in a province (i) was positively associated with longer time mothers spent on child care; (ii) moderated the association of improvements in maternal physical health and shorter time mothers spent on child care; and (iii) moderated the association of family conflicts and more family educational expenditure. Conclusion: Findings indicate that decreased parental psychological and physical well-being foretells reductions in monetary and non-monetary investment in early learning and care at home. Regional pandemic risk undermines maternal investment in early learning and care, especially for those with pre-existing physical conditions.